A The Effectiveness of Engklek and Zig-Zag Game Exercises on the Static and Dynamic Balance of Intellectually Impaired Children - Wijayanto, Adhi; Soentoyo, Tommy; Sumartiningsih, Sri (Journal of Physical Education and Sports, 2023)
This research uses quantitative quasi-experimental methods with a two factorial design. The aim of this research is to find out and analyze how effective the Zig-Zag and Engklek game exercises are on the static and dynamic balance of children with special needs who are mentally retarded in physical education learning at SLB Demak Regency. The population in this study were mentally retarded students at SDLB Demak Regency with a total of 36 children. The sampling technique used purposive sampling to obtain a sample size of 20 children. The data analysis technique uses multivariate analysis of variance (Manova) at the significance level (α: 0.05). The results of this study: 1) The Zig-zag training group with normal weight experienced an average increase of 13.4 in static balance and experienced an average increase of 10 in dynamic balance, while children who were obese were given Zig-zag training. experienced an average increase of 3 in static balance and experienced an average increase of 6 in dynamic balance. 2) The group that had normal body weight experienced an average increase of 11.2 in static balance and an average increase of 10 in dynamic balance, while the group that had an obese body weight experienced an average increase of 11.2 in playing crankshaft. 6 in static balance and experienced an average increase of 6 in dynamic balance. The conclusion of this research is the effectiveness of Zig-zag and crank game exercises on the static balance and dynamic balance of Intellectually Disabled Children in Physical Education Learning at Special Schools in Demak Regency.